An Analysis of Students’ Grammar Ability in Writing Procedure Text at SMK Negeri 3 Pekanbaru - Adzania Eria Teagu (Jurnal Pendidikan dan Sastra Inggris, 2025)
This research aims to analyze students grammar ability in writing procedure texts at SMK Negeri 3 Pekanbaru. The focus of the study is on students grammatical aspects, particularly the use of imperative sentences, simple present tense, vocabulary choice, and punctuation. This study employed a descriptive qualitative approach with data collected through documentation (writing tasks) and interviews. The sample consisted of 18 eleventh-grade students of the Fashion Design department, selected randomly from a population of 120 students. The findings revealed that, in general, students were able to compose procedure texts with appropriate structures (goals, materials, and steps). However, errors were still found in verb choices, vocabulary spelling, and punctuationusage. The study concludes that students' grammar ability in writing procedure texts falls into the fair category, yet it needs improvement through consistent practice and greater attention to grammatical rules. This research is expected to provide input for teachers in improving students' writing skills and serve as a reference for future researchers.